Severe Caffeine Intoxication Treated With Hemodialysis: A Case Report - Elbokl, Mohamed (Kidney Med, 2021)
Caffeine is well known for its central nervous system–stimulating effect. Toxicity may occur following high-dose caffeine ingestions. We describe a case of caffeine intoxication secondary to reported ingestion of a large dose of caffeine (60,000 mg in tablet form) with an initial serum caffeine level of 608 μmol/L (known lethal serum level starting from 412 μmol/L). This case demonstrates the key clinical manifestations of caffeine intoxication and the effect of its associated massive adrenergic surge with neurologic symptoms, cardiovascular instability, metabolic abnormalities, and the significant risk of mortality. We highlight important kidney management considerations, including protective measures against electrolyte disturbances such as hypokalemia and hypophosphatemia, and the use of prolonged hemodialysis for caffeine elimination. We share our practical decision making and approach to dialysis discontinuation if serum caffeine level reporting is unavailable or delayed.